Asymmetric Nickel‐Catalysed Cross‐Hydrovinylation of Two Terminal Alkenes. Issue 11 (20th April 2015) - Hilt, Gerhard
<x xml:space="preserve">Abstract</x> Pushing the boundaries: The asymmetric 1, 2‐hydrovinylation of styrene derivatives with terminal alkenes is realised by using a nickel catalyst and specially designed chiral NHC ligands to achieve a new level of complexity for the tail‐to‐tail cross‐coupling of alkenes by CH activation.